Formation of a CoMn‐Layered Double Hydroxide/Graphite Supercapacitor by a Single Electrochemical Step. Issue 21 (21st September 2022) - Roy, Atanu; Schoetz, Theresa; Gordon, Leo W.; Yen, Hung‐Ju; Hao, Qingli; Mandler, Daniel
Abstract: Hybrid electric storage systems that combine capacitive and faradaic materials need to be well designed to benefit from the advantages of batteries and supercapacitors. The ultimate capacitive material is graphite (GR), yet high capacitance is usually not achieved due to restacking of its sheets. Therefore, an appealing approach to achieve high power and energy systems is to embed a faradaic 2D material in between the graphite sheets. Here, a simple one‐step approach was developed, whereby a faradaic material [layered double hydroxide (LDH)] was electrochemically formed inside electrochemically exfoliated graphite. Specifically, GR was exfoliated under negative potentials by Co II and, in the presence of Mn II, formed GR‐CoMn‐LDH, which exhibited a high areal capacitance and energy density. The high areal capacitance was attributed to the exfoliation of the graphite at very negative potentials to form a 3D foam‐like structure driven by hydrogen evolution as well as the deposition of CoMn‐LDH due to hydroxide ion generation inside the GR sheets. The ratio between the Co II and Mn II in the CoMn‐LDH was optimized and analyzed, and the electrochemical performance was studied. Analysis of a cross‐section of the GR‐CoMn‐LDH confirmed the deposition of LDH inside the GR layers. The areal capacitance of the electrode was 186 mF cm −2 at a scan rate of 2 mV s −1 . Finally, an asymmetric supercapacitor was assembled with GR‐CoMn‐LDH and exfoliated graphite as the positive and negative electrodes, respectively, yielding an energy density of 96.1 μWh cm −3 and a power density of 5 mW cm −3 . Abstract : Two at once : Simultaneous electrochemical exfoliation of graphite foil and deposition of CoMn‐layered double hydroxides (LDHs) are performed in a solution consisting of Co 2+ and Mn 2+ ions. The asymmetric supercapacitor formed with the CoMn‐LDH exhibits a wide potential window of 1.8 V along with high energy and power density.